Zirconia sol and method for producing zirconia sol
By dropping ammonia water into the aqueous zirconium oxychloride solution for neutralization, zirconium oxide sol with specific particle size and shape is solved, and the existing zirconium oxide sol is insufficient in polishing abrasive particles, achieving a more efficient precision polishing effect.
Patent Information
- Application Number
- CN202480004026.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-30
- Filing Date
- 2024-03-22
- Publication Date
- 2025-04-11
AI Technical Summary
The existing zirconia sols have problems with insufficient rate and smoothness in polishing abrasive particles, especially in precision polishing such as semiconductors.
By adding ammonia water dropwise to the zirconium oxychloride aqueous solution for neutralization, the concentration of zirconium oxychloride aqueous solution and ammonia water concentration are controlled to be 10 mass %, and the capacity of ammonia water droplets is limited to 1.0 ml, to generate a zirconia sol with a particle diameter D50 of 50 nm or more and 250 nm or less, and to contain more than 40% of particles with irregular angular shapes.
Zirconia sols with higher rates and higher smoothness (low surface roughness) in precision polishing, especially in the fields of semiconductors, etc.
Smart Images

Figure CN119816473A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a zirconium oxide sol and a method for producing the zirconium oxide sol. Background Art
[0002] Zirconia sol is used for raw material powder of fine ceramics, precision polishing agent, cosmetics, filler for paint, zirconium oxide thin film, etc. (see, for example, Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 02-137732 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] The present invention aims to provide a zirconium oxide sol which is more suitable for use as polishing abrasive particles and also to provide a method for preparing the zirconium oxide sol.
[0008] Solutions for solving problems
[0009] The present invention provides the following technical solutions:
[0010] [1] A zirconium oxide sol, characterized in that:
[0011] Particle size D 50 In the range of 50nm to 250nm,
[0012] The ratio X obtained by the following steps is 40% or more,
[0013] <Steps>
[0014] A transmission electron microscope image containing more than 20 isolated particles was obtained;
[0015] For each isolated particle in the transmission electron microscope image, the following operations 1) to 5) are performed:
[0016] 1) Find the circumscribed circle and the inscribed circle with the same center as the circumscribed circle.
[0017] 2) Find the ratio of the diameter of the circumscribed circle to the diameter of the inscribed circle [(diameter of the circumscribed circle) / (diameter of the inscribed circle)],
[0018] 3) for all isolated particles in the transmission electron microscope image, the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is calculated.
[0019] 4) Count the number of isolated particles A whose ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is greater than 2.0,
[0020] 5) Find the ratio X of the isolated particle A to all isolated particles,
[0021] (Ratio X (%)) = [(Number of isolated particles A) / (Number of all isolated particles)] × 100.
[0022] The particles whose ratio [(circumscribed circle diameter) / (inscribed circle diameter)] is greater than 2.0 can be said to be irregularly shaped particles with edges and corners. According to the configuration of [1], the ratio X is greater than 40% and contains a certain number of irregularly shaped particles with edges and corners. The zirconium oxide sol having such particles can be used as polishing abrasive grains.
[0023] In particular, according to the configuration of [1], the particle size D 50 In other words, according to the configuration of [1], the particle size D 50 The particle size is between 50nm and 250nm and contains a certain number of irregular angular particles. 50 Zirconia sol having a diameter of 50 nm or more and 250 nm or less and containing irregularly shaped particles is expected to have a higher rate and higher smoothness (lower surface roughness) in precision polishing than existing products, especially in precision polishing of semiconductors and the like.
[0024] Furthermore, the present invention also provides the following technical solutions:
[0025] [2] The zirconium oxide sol according to [1], wherein the ratio X is 50% or more.
[0026] When the ratio X is 50% or more, the abrasive grains can be more suitably used as polishing abrasive grains.
[0027] Furthermore, the present invention also provides the following technical solutions:
[0028] [3] The zirconium oxide sol according to [1] or [2], wherein the particle size D 50 Below 200nm.
[0029] When the particle size D 50 When the particle size is 200 nm or less, the abrasive grains can be more suitably used as polishing abrasive grains.
[0030] Furthermore, the present invention also provides the following technical solutions:
[0031] [4] The method for producing a zirconium oxide sol according to any one of [1] to [3], comprising:
[0032] Step A, adding aqueous ammonia to the zirconium oxychloride aqueous solution for neutralization, wherein:
[0033] The concentration of the zirconium oxychloride aqueous solution is 10% by mass or more (value calculated as ZrO2, the same below),
[0034] The concentration of the ammonia water is 10% by mass or more,
[0035] The volume of the droplet of the ammonia water dropped in the step A is 1.0 ml or less.
[0036] According to the configuration [4], first, aqueous ammonia is used as a neutralizing agent. Since aqueous ammonia is used as a neutralizing agent, the zirconia sol of [1], i.e., the zirconia sol in which the ratio X is 40% or more, can be obtained. The reason for this is not clear, but the inventors speculate that aqueous ammonia is a weak base compared to a strong base such as an aqueous sodium hydroxide solution, so the generation of the nucleus of the particle is slow, and the particle size is larger than when a strong base is used, and the shape is irregular.
[0037] Moreover, according to the structure of [4], in the neutralization step A, ammonia water within a specific concentration range is added dropwise to an aqueous zirconium oxychloride solution within a specific concentration range, and the volume of the droplets is controlled within a specific range. Specifically, ammonia water with a concentration of 10% by mass or more is added dropwise to an aqueous zirconium oxychloride solution with a concentration of 10% by mass or more. And, the droplet volume of the added ammonia water is 1.0 ml or less. Thus, the zirconium oxide sol of [1] can be obtained, that is, the zirconium oxide sol in which the ratio X is 40% or more. The reason is not clear, but we believe that the process by which the aqueous zirconium oxychloride solution reacts with ammonia water to generate zirconium hydroxide is as follows (1) and (2):
[0038] (1) Zirconium oxychloride reacts with ammonia to form a zirconium hydroxide core (presumably a cluster similar to that represented by the chemical formula {Zr(OH)4}n);
[0039] (2) Agglomeration between zirconium hydroxide nuclei and particle growth of zirconium hydroxide nuclei proceed simultaneously.
[0040] In this regard, the inventors speculate that the concentration of the initial zirconium oxychloride aqueous solution, the concentration of the ammonia water, and the droplet volume when the ammonia water is added are the determining factors of the nucleation rate and its generation density, and therefore the controlling factors of the balance between the aggregation of nuclei and the particle growth of nuclei in (2). The particle characteristics (particle size and shape, etc.) of the finally obtained zirconium oxide sol should be determined by the particle characteristics (particle size and shape, etc.) of the zirconium hydroxide generated in step A.
[0041] Thus, according to the configuration [4], by using aqueous ammonia as a neutralizing agent, setting the concentration of the zirconium oxychloride aqueous solution to 10% by mass or more, and dropping aqueous ammonia in the aqueous zirconium oxychloride solution with a drop size of the aqueous ammonia being controlled to be less than 1.0 ml during the dropping process, a large number of particles having a large particle size and irregular shape can be obtained. That is, a zirconium oxide sol having the ratio X of 40% or more can be obtained.
[0042] On the other hand, if the concentration of the zirconium oxychloride aqueous solution is less than 10 mass % and the concentration of the ammonia water is less than 10 mass %, the droplet volume of the ammonia water when dripping exceeds 1.0 ml, the balance of (2) is no longer appropriate, and it is difficult to obtain the zirconium oxide sol of [1] described above.
[0043] Effects of the Invention
[0044] According to the present invention, a zirconium oxide sol more suitable for use as polishing abrasive grains can be provided, and a method for producing the zirconium oxide sol can also be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 A diagram for explaining the circumscribed circle and inscribed circle of an isolated particle in a transmission electron microscope image. DETAILED DESCRIPTION
[0046] The embodiments of the present invention are described below. However, the present invention is not limited to these embodiments. In addition, in this specification, zirconium oxide (zirconium dioxide) is ordinary zirconium oxide containing 10% by mass or less of an impurity metal compound containing hafnium. In addition, in this specification, expressions such as "containing" and "including" include the concepts of "containing", "including", "substantially consisting of", and "consisting only of".
[0047] [Zirconium oxide sol]
[0048] Hereinafter, an example of the zirconium oxide sol according to the present embodiment will be described. However, the zirconium oxide sol of the present invention is not limited to the following example.
[0049] In the zirconium oxide sol of this embodiment,
[0050] Particle size D 50 In the range of 50nm to 250nm,
[0051] The ratio X obtained by the following steps is 40% or more,
[0052] <Steps>
[0053] A transmission electron microscope image containing more than 20 isolated particles was obtained;
[0054] For each isolated particle in the transmission electron microscope image, the following operations 1) to 5) are performed:
[0055] 1) Find the circumscribed circle and the inscribed circle with the same center as the circumscribed circle.
[0056] 2) Find the ratio of the diameter of the circumscribed circle to the diameter of the inscribed circle [(diameter of the circumscribed circle) / (diameter of the inscribed circle)],
[0057] 3) for all isolated particles in the transmission electron microscope image, the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is calculated.
[0058] 4) Count the number of isolated particles A whose ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is greater than 2.0,
[0059] 5) Find the ratio X of the isolated particle A to all isolated particles,
[0060] (Ratio X (%)) = [(Number of isolated particles A) / (Number of all isolated particles)] × 100.
[0061] As mentioned above, the particle size D of the zirconium oxide sol 50 In the range of 50nm to 250nm.
[0062] The particle size D 50 It is preferably 200 nm or less, more preferably 180 nm or less, and further preferably 150 nm or less.
[0063] The particle size D 50 It is preferably 55 nm or more, more preferably 60 nm or more, and even more preferably 65 nm or more.
[0064] The particle size D 50 The diameter is preferably from 55 nm to 200 nm, more preferably from 60 nm to 180 nm, and even more preferably from 65 nm to 150 nm.
[0065] In more detail, the particle size D 50 The determination method is based on the method described in the examples.
[0066] The ratio X of the zirconium oxide sol obtained according to the following steps is greater than 40%,
[0067] <Steps>
[0068] A transmission electron microscope image containing more than 20 isolated particles was obtained;
[0069] For each isolated particle in the transmission electron microscope image, the following operations 1) to 5) are performed:
[0070] 1) Find the circumscribed circle and the inscribed circle with the same center as the circumscribed circle.
[0071] 2) Find the ratio of the diameter of the circumscribed circle to the diameter of the inscribed circle [(diameter of the circumscribed circle) / (diameter of the inscribed circle)],
[0072] 3) for all isolated particles in the transmission electron microscope image, the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is calculated.
[0073] 4) Count the number of isolated particles A whose ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is greater than 2.0,
[0074] 5) Find the ratio X of the isolated particle A to all isolated particles,
[0075] (Ratio X (%)) = [(Number of isolated particles A) / (Number of all isolated particles)] × 100.
[0076] The ratio X is preferably 45% or more, more preferably 50% or more, further preferably 55% or more, and further preferably 60% or more.
[0077] The larger the ratio X is, the better, for example, it is 99% or less, 90% or less, etc.
[0078] The ratio X is preferably 45% to 99%, more preferably 50% to 99%, further preferably 55% to 90%, and particularly preferably 60% to 85%.
[0079] In more detail, the ratio X is a value obtained according to the method described in the embodiment.
[0080] The particles having the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] of 2.0 or more can be said to be irregularly shaped particles with edges and corners. According to the zirconia sol, the ratio X is 40% or more, and contains a certain number or more of irregularly shaped particles with edges and corners. The zirconia sol having such particles can be used as polishing abrasive grains.
[0081] In particular, according to the zirconium oxide sol, the particle size D 50 In other words, according to the zirconia sol, the particle size D 50 The particle size is between 50nm and 250nm, and contains a certain number of irregular particles with edges and corners. 50Zirconia sol having a diameter of 50 nm to 250 nm and containing irregularly shaped particles is expected to have a higher rate and higher smoothness (low surface roughness) in precision polishing than existing products, especially in precision polishing of semiconductors and the like.
[0082] The concentration of the zirconium oxide sol is not particularly limited, and is generally 5% by mass or more and 80% by mass or less in terms of ZrO2. When the concentration of the zirconium oxide sol is 5% by mass or more, it is possible to prevent the zirconium oxide concentration from being reduced when diluted with other solvents. When the concentration of the zirconium oxide sol is 80% by mass or less, it is possible to suppress the thickening of the sol and provide excellent stability.
[0083] The concentration of the zirconium oxide sol is more preferably 10% by mass or more, and further preferably 15% by mass or more.
[0084] The concentration of the zirconium oxide sol is more preferably 70% by mass or less, and further preferably 60% by mass or less.
[0085] The concentration of the zirconium oxide sol is more preferably 10% by mass or more and 70% by mass or less, and further preferably 15% by mass or more and 60% by mass or less.
[0086] The dispersion medium of the zirconia sol is not particularly limited, and may be a hydrophilic organic solvent such as water, methanol, ethanol, 2-propanol, acetone, ether, or a mixture of more than one hydrophilic organic solvent. The dispersion medium of the zirconia sol is usually preferably water (pure water or ion-exchanged water).
[0087] The pH of the dispersion medium of the zirconia sol is not particularly limited, but is usually preferably 7 or less, and more preferably 1 or more and 6 or less. When the pH of the dispersion medium of the zirconia sol is 7 or less, the pH is far from the isoelectric point of zirconia, and the stability is improved.
[0088] <Polishing performance>
[0089] The zirconium oxide sol is diluted with pure water to a liquid with a ZrO2 content of 5.0% by mass as a polishing agent. Preferably, the polishing rate when polishing soda glass (surface roughness Ra (arithmetic mean roughness): 0.3 μm or more and 0.5 μm or less) is 0.12 μm / min or more, and the surface roughness Ra of the polished surface is 0.6 nm or less.
[0090] When the polishing rate is 0.12 μm / min or more and the surface roughness Ra of the polished surface is 0.6 nm or less, a polished surface with low surface roughness can be obtained in a short time.
[0091] The polishing rate is more preferably 0.13 μm / min or more, and further preferably 0.14 μm / min or more.
[0092] As long as the surface roughness does not exceed a certain level, the higher the polishing rate, the better. Specifically, the polishing rate is more preferably 1.0 μm / min or less, and further preferably 0.7 μm / min or less.
[0093] The polishing rate is more preferably 0.12 μm / min to 1.0 μm / min, and even more preferably 0.13 μm / min to 0.7 μm / min.
[0094] The surface roughness Ra of the polished surface is more preferably 0.55 nm or less, and further preferably 0.50 nm or less.
[0095] The smaller the surface roughness Ra of the polished surface is, the better, for example, it is greater than 0.10 nm, greater than 0.20 nm, etc.
[0096] The surface roughness Ra of the polished surface is more preferably from 0.10 nm to 0.55 nm, and further preferably from 0.20 nm to 0.50 nm.
[0097] The zirconia sol of the present embodiment can be obtained, for example, by the following method for producing zirconia sol.
[0098] [Method for producing zirconium oxide sol]
[0099] Hereinafter, an example of a method for producing zirconium oxide sol will be described, but the method for producing zirconium oxide sol is not limited to the following example.
[0100] The method for producing the zirconium oxide sol of this embodiment includes:
[0101] Step A, adding aqueous ammonia to the zirconium oxychloride aqueous solution for neutralization, wherein:
[0102] The concentration of the zirconium oxychloride aqueous solution is 10% by mass or more,
[0103] The concentration of the ammonia water is 10% by mass or more,
[0104] The volume of the droplet of the ammonia water dropped in the step A is 1.0 ml or less.
[0105] <Process A>
[0106] First, in step A, aqueous ammonia is added dropwise to an aqueous zirconium oxychloride solution for neutralization.
[0107] In the present embodiment, aqueous ammonia is used as a neutralizing agent for zirconium oxychloride.
[0108] The concentration of the ammonia water is 10% by mass or more.
[0109] The concentration of the aqueous ammonia is preferably 15% by mass or more, more preferably 20% by mass or more.
[0110] The concentration of the aqueous ammonia has no particular upper limit, and is, for example, 30% by mass or less, 28% by mass or less, or the like.
[0111] The concentration of the aqueous ammonia is preferably 15% by mass or more and 30% by mass or less, and more preferably 20% by mass or more and 28% by mass or less.
[0112] The concentration of the zirconium oxychloride aqueous solution is 10% by mass or more.
[0113] The concentration of the zirconium oxychloride aqueous solution is preferably 15% by mass or more, and more preferably 18% by mass or more.
[0114] The concentration of the zirconium oxychloride aqueous solution has no particular upper limit, and is, for example, 28% by mass or less, 25% by mass or less, or the like.
[0115] The concentration of the zirconium oxychloride aqueous solution is preferably 15% by mass or more and 28% by mass or less, and more preferably 18% by mass or more and 25% by mass or less.
[0116] The volume of the droplet of the ammonia water dropped in the step A is 1.0 ml or less.
[0117] The volume of the droplet is preferably 0.7 ml or less, more preferably 0.5 ml or less.
[0118] The smaller the volume of the droplet is, the better, for example, 0.05 ml or more, 0.1 ml or more, etc.
[0119] The volume of the droplet is preferably 0.05 ml to 0.7 ml, more preferably 0.1 ml to 0.5 ml.
[0120] The dripping time of the ammonia water in the step A is not particularly limited. For example, when 1000 ml of ammonia water is dripped into 1000 ml of the zirconium oxychloride aqueous solution, the dripping time is preferably 10 minutes to 120 minutes.
[0121] The dripping time is more preferably 90 minutes or less, and further preferably 60 minutes or less.
[0122] The dropping time is not particularly limited as long as it is within a range that allows the reaction to proceed appropriately, and is, for example, 15 minutes or longer, 20 minutes or longer, etc.
[0123] The dripping time is preferably from 15 minutes to 90 minutes, and more preferably from 20 minutes to 60 minutes.
[0124] The temperature of the zirconium oxychloride aqueous solution and the temperature of the ammonia water before the step A is performed are not particularly limited, and may be, for example, ambient temperature (for example, within a range of 20° C. to 40° C.). In addition, the temperature of the zirconium oxychloride aqueous solution and the temperature of the ammonia water before the step A is performed may also be adjusted in advance.
[0125] When temperature adjustment is performed, the temperature of the zirconium oxychloride aqueous solution and the temperature of the ammonia water before the step A are preferably 50° C. or lower, and more preferably 40° C. or lower.
[0126] When temperature adjustment is performed, the lower limits of the temperature of the zirconium oxychloride aqueous solution and the temperature of the ammonia water before the step A are not particularly limited, and may be within a range that allows the reaction to proceed appropriately, for example, 5° C. or above, 10° C. or above.
[0127] When temperature adjustment is performed, the temperature of the zirconium oxychloride aqueous solution and the temperature of the ammonia water before the step A are preferably 5° C. to 50° C., more preferably 10° C. to 40° C.
[0128] According to the method for producing the zirconia sol, since aqueous ammonia is used as a neutralizing agent, the zirconia sol, that is, the zirconia sol in which the ratio X is 40% or more can be obtained.
[0129] Furthermore, according to the method for producing the zirconium oxide sol, in the neutralization step A, ammonia water having a concentration of 10 mass % or more is added dropwise to the zirconium oxychloride aqueous solution having a concentration of 10 mass % or more, and the droplet volume of the ammonia water added dropwise is 1.0 ml or less, so that many particles having a large particle size and irregular shape can be obtained. That is, a zirconium oxide sol having the ratio X of 40% or more can be obtained.
[0130] Thus, according to the method for producing zirconium oxide sol, by using ammonia water as a neutralizing agent, setting the concentration of zirconium oxychloride aqueous solution to 10 mass % or more, setting the concentration of ammonia water to 10 mass % or more, and setting the droplet volume of ammonia water to 1.0 ml or less when dropping, many particles with large particle sizes and irregular shapes can be obtained. That is, a zirconium oxide sol with the ratio X of 40% or more can be obtained.
[0131] After the step A, stirring is performed as needed to make the mixture uniform, thereby obtaining a precipitate of zirconium hydroxide. The stirring time is not particularly limited, and is, for example, 15 minutes to 120 minutes.
[0132] Then, the zirconium hydroxide is washed as needed. The washing is performed until, for example, the Cl concentration is below a predetermined concentration. The predetermined concentration is preferably, for example, below 0.01%. The washing method is not particularly limited, and for example, the following operation can be repeated: filtering the zirconium hydroxide and dispersing it with ion exchange water.
[0133] Next, an acid is added as a disintegrating agent.
[0134] The degumming agent for zirconium hydroxide is not particularly limited, as long as it is a water-soluble inorganic acid or organic acid, such as hydrochloric acid, nitric acid, sulfuric acid, acetic acid, lactic acid, citric acid, tartaric acid, malic acid, mandelic acid, etc. Hydrochloric acid and nitric acid are preferred. The reason is that even if there is excess hydrochloric acid or nitric acid in the zirconium oxide sol, it can be easily removed by purification in water after the zirconium oxide sol is generated.
[0135] The amount of the debonding agent added is acid / ZrO2 (molar ratio) = 0.01 to 3, more preferably 0.1 to 1.5.
[0136] When the acid / ZrO2 (molar ratio) is 0.01 or more, zirconium hydroxide can be fully debonded. In addition, even if the acid / ZrO2 (molar ratio) exceeds 3, the quantitative effect is small, so when the acid / ZrO2 (molar ratio) is 3 or less, it is more economical.
[0137] Next, heating and aging are performed to debond the zirconium hydroxide. From the viewpoint of productivity, the temperature of the heating and aging is preferably 80°C or higher, more preferably 90°C or higher. The heating temperature is preferably 110°C or lower, more preferably 105°C or lower. The heating temperature is preferably 80°C or higher and 110°C or lower, more preferably 90°C or higher and 105°C or lower.
[0138] From the viewpoint of productivity, the duration of the heating and aging is preferably 24 hours or more, more preferably 48 hours or more. The duration of the heating and aging is preferably 120 hours or less, more preferably 100 hours or less. The duration of the heating and aging is preferably 24 hours or more and 120 hours or less, more preferably 48 hours or more and 100 hours or less.
[0139] Then, after cooling to room temperature, ultrafiltration may be performed to concentrate the zirconium oxide sol.
[0140] The excess acid added can be easily removed by ultrafiltration.
[0141] The method for producing the zirconium oxide sol according to the present embodiment has been described above.
[0142] Example
[0143] The present invention is described in detail below with reference to examples, but the present invention is not limited to the following examples unless it exceeds the gist of the present invention. It should be noted that the zirconium oxide sol in the examples and comparative examples contains 1 to 3 mass % (calculated by the following formula (X)) of hafnium as an inevitable impurity relative to zirconium.
[0144] <Formula (X)>
[0145] ([Mass of hafnium oxide] / ([Mass of zirconium oxide]+[Mass of hafnium oxide]))×100 (%)
[0146] The maximum and minimum values of the content of each component shown in the following examples are irrelevant to the contents of other components and should be regarded as the preferred minimum and preferred maximum values of the present invention.
[0147] Furthermore, the maximum and minimum values of the measured values shown in the following Examples have nothing to do with the content (composition) of each component, and should be regarded as the preferred minimum and maximum values of the present invention.
[0148] [Preparation of Zirconia Sol]
[0149] (Example 1)
[0150] 1000g of zirconium oxychloride aqueous solution (10% by mass in terms of ZrO2) adjusted to 25°C in a thermostatic bath was dripped with 1380g of ammonia water (10% by mass) also adjusted to 25°C over 30 minutes. At this time, the number of roots and the dripping speed of the liquid inlet pipe were adjusted so that the volume of the ammonia water droplets was within the range of 0.1 to 0.5ml. Then, stirring was continued for 30 minutes to obtain a precipitate of zirconium hydroxide. The washing operation was repeated, that is, the zirconium hydroxide was filtered and dispersed again with ion exchange water. The operation was performed until the Cl concentration was below 0.01%.
[0151] The concentration of the washed zirconium hydroxide was 31.9% by mass in terms of ZrO2. 299 g of ion exchange water and 39.1 g of nitric acid (60% by mass) were mixed with the obtained 300 g of zirconium hydroxide, and the prepared slurry was kept at 100° C. under reflux for 48 hours while stirring, and the obtained zirconium oxide sol precursor was purified by ultrafiltration, thereby obtaining the zirconium oxide sol of Example 1.
[0152] (Example 2 to Example 4, Comparative Example 1)
[0153] Zirconium oxide sols of Examples 2 to 4 and Comparative Example 1 were obtained in the same manner as in Example 1, except that the concentration of the zirconium oxychloride aqueous solution and / or the concentration of ammonia water was changed as described in Table 1. It should be noted that "ZOC" in Table 1 refers to zirconium oxychloride.
[0154] (Comparative Example 2 to Comparative Example 3)
[0155] Zirconium oxide sols of Comparative Examples 2 and 3 were obtained in the same manner as in Example 1 except that the concentration of the zirconium oxychloride aqueous solution and / or the concentration of ammonia water and the volume of ammonia water droplets were changed as described in Table 1.
[0156] (Comparative Example 4)
[0157] A zirconium oxide sol of Comparative Example 4 was obtained in the same manner as in Example 2, except that 15% by mass of caustic soda (sodium hydroxide aqueous solution) was used instead of ammonia water.
[0158] (Comparative Example 5)
[0159] A zirconia sol of Comparative Example 5 was obtained in the same manner as in Example 1 except that a zirconia sol precursor obtained by maintaining an aqueous zirconium oxychloride solution diluted with pure water to 1 mass % as ZrO2 at 100°C under reflux for 60 hours was used.
[0160] [Particle size D 50 Determination of
[0161] The zirconium oxide sols of the examples and comparative examples were diluted with ion exchange water to 0.1 mass % in terms of ZrO2 and placed in an apparatus (dynamic light scattering particle size distribution measuring apparatus ("Zetasizer Nano ZS" manufactured by Malvern Panalytical)) to measure the particle size D of the zirconium oxide sol. 50 The results are shown in Table 1.
[0162] <Measurement conditions>
[0163] Measurement temperature: 25℃;
[0164] Scattering angle: 173°;
[0165] Dispersion: ZrO2;
[0166] Dispersion medium: water;
[0167] Sample pool: genuine disposable sample pool.
[0168] [Measurement of particle shape]
[0169] First, TEM images (transmission electron microscope images) of the zirconium oxide sols of the examples and comparative examples were obtained. The TEM images were taken using a transmission electron microscope (manufactured by Hitachi, Ltd., product name: HV-8100), and the size of one field of view was 1.15 μm×0.90 μm.
[0170] Next, the number of isolated particles was counted by visual inspection. Specifically, the number of particles whose circumscribed circle circumscribed to the particle has a diameter of 50nm or more was counted. If there are multiple circumscribed circles circumscribed to the particle, the circumscribed circle with the smallest ratio of the diameter of the circumscribed circle to the diameter of the inscribed circle (concentric inscribed circle) with the same center as the circumscribed circle (refer to "2" below) is used. It should be noted that the reason why particles whose circumscribed circle circumscribed to the particle has a diameter of less than 50nm are not counted is because the effect of such particles as polishing agents is very low.
[0171] When the number of isolated particles is more than 20, the TEM image is used as the image to be evaluated. When the number of isolated particles is less than 20, TEM images of other fields of view are taken, and the images are repeatedly taken until a TEM image with more than 20 isolated particles is obtained.
[0172] For each isolated particle in the obtained TEM image (isolated particle to be counted), the following operations are performed:
[0173] 1) First, the circumscribed circle of the particle and the inscribed circle with the same center as the circumscribed circle (concentric inscribed circle) were calculated (refer to Figure 1 ). It should be noted that the definitions of the circumscribed circle and the inscribed circle are the same as those of the MCC method of roundness in JIS B 7451:1997.
[0174] 2) Next, the ratio of the diameter of the circumscribed circle to the diameter of the inscribed circle was calculated [(diameter of the circumscribed circle) / (diameter of the inscribed circle)].
[0175] 3) For all isolated particles in the TEM image (all isolated particles to be counted), the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] was calculated.
[0176] 4) Count the number of isolated particles (hereinafter also referred to as "isolated particles A") for which the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is 2.0 or more,
[0177] 5) The existence ratio of isolated particle A to all isolated particles (all isolated particles to be counted) (hereinafter also referred to as "ratio X") is calculated.
[0178] (Ratio X (%)) = [(Number of isolated particles A) / (Number of all isolated particles)] × 100.
[0179] The results are shown in Table 1.
[0180] [Polishing performance evaluation]
[0181] The zirconium oxide sols of the examples and comparative examples were diluted with pure water to a ZrO2 content of 5.0 mass % as a polishing agent, and soda glass (Ra: 0.3 to 0.5 μm) polishing was performed, and the polishing rate and the surface roughness Ra of the polished surface were measured.
[0182] The polishing conditions are as follows:
[0183] Substrate (object to be polished): soda glass (surface roughness Ra (arithmetic mean roughness): 0.3 μm or more and 0.5 μm or less);
[0184] Polishing device: single-side polishing device (EJ-380N manufactured by ENGIS);
[0185] Polishing pad: suede pad;
[0186] Polishing load: 100g / cm 2 (9.8kPa);
[0187] Rotation speed of turntable: 80rpm (linear speed: 9.5m / min);
[0188] Polishing time: 15 minutes;
[0189] Feed rate of polishing composition: 10 mL / min;
[0190] Measuring area of the object to be polished: 0.143×0.107mm (surface roughness);
[0191] Pitch: 0.164μm;
[0192] The polishing speed is measured by measuring the weight of the substrate before and after polishing and calculating based on the difference.
[0193] The surface roughness (arithmetic mean roughness (Ra)) of the polished surface of the polished object after polishing was measured using a non-contact 3D shape measurement / surface roughness measurement machine "NewView5032" manufactured by AMETEC under the condition of a viewing angle of 0.143×0.107 mm. The results are shown in Table 1.
[0194] Table 1
[0195]
Claims
1. A zirconium oxide sol, characterized in that: Particle size D 50 In the range of 50nm to 250nm, The ratio X obtained by the following steps is 40% or more, <Steps> A transmission electron microscope image containing more than 20 isolated particles was obtained; For each isolated particle in the transmission electron microscope image, the following operations 1) to 5) are performed: 1) Find the circumscribed circle and the inscribed circle with the same center as the circumscribed circle. 2) Find the ratio of the diameter of the circumscribed circle to the diameter of the inscribed circle [(diameter of the circumscribed circle) / (diameter of the inscribed circle)], 3) for all isolated particles in the transmission electron microscope image, the ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is calculated. 4) Count the number of isolated particles A whose ratio [(diameter of the circumscribed circle) / (diameter of the inscribed circle)] is greater than 2.0, 5) Find the ratio X of the isolated particle A to all isolated particles, (Ratio X (%)) = [(Number of isolated particles A) / (Number of all isolated particles)] × 100.
2. The zirconium oxide sol according to claim 1, characterized in that The ratio X is greater than 50%.
3. The zirconium oxide sol according to claim 1 or 2, characterized in that: The particle size D 50 Below 200nm.
4. A method for producing a zirconium oxide sol according to claim 1 or 2, characterized in that: include: Step A, adding aqueous ammonia to the zirconium oxychloride aqueous solution for neutralization, wherein: The concentration of the zirconium oxychloride aqueous solution is 10% by mass or more, The concentration of the ammonia water is 10% by mass or more, The volume of the droplet of the ammonia water dropped in the step A is 1.0 ml or less.
Citation Information
Patent Citations
Production of aqueous weakly acidic crystallized zirconia-based sol
JP1990137732A